Modification of σ‐Donor Properties of Terminal Carbide Ligands Investigated Through Carbide–Iodine Adduct Formation. (9th September 2016) - Reinholdt, Anders; Vosch, Tom; Bendix, Jesper
Abstract: The terminal carbide ligands in [(Cy3 P)2 X2 Ru≡C] complexes (X=halide or pseudohalide) coordinate molecular iodine, affording charge‐transfer complexes rather than oxidation products. Crystallographic and vibrational spectroscopic data show the perturbations of iodine to vary with the auxiliary ligand sphere on ruthenium, demonstrating the σ‐donor properties of carbide complexes to be tunable.